PRODUCTION AND BIOACTIVITY POTENTIAL OF THREE RECOMBINANT GROWTH HORMONES OF FARMED FISH - Alimuddin Alimuddin; Indra Lesmana; Agus Oman Sudrajat; Odang Carman; Irvan Faizal (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2010)
This study was aimed to produce recombinant growth hormone (rGH) from giant grouper (Epinephelus lanceolatus), giant gouramy (Osphronemus gouramy) and common carp (Cyprinus carpio) and compare their bioactivity potential by means of inducing the growth hormone of juvenile Nile tilapia (Oreochromis niloticus) as the model. DNA fragment encoding mature GH protein of giant grouper (El-mGH), giant gouramy (Og-mGH) and common carp (Cc-mGH) was amplified by PCR method. The purified PCR products were ligated to pCold-1 to generate pCold/El-mGH, pCold/OgmGH, and pCold/Cc-mGH protein expression vector, respectively. Each of the expression vectors was transformed into the Escherichia coli BL21. E. coli BL21 was cultured using 2xYT medium and protein production was induced by cold shock at 15±1oC for overnight. The inclusion bodies of E. coli transformants containing protein expression vector were isolated by sonication method, and rGH production was analyzed by SDS-PAGE. Juvenile of Nile tilapia of average body weight of 12.41±3.28 g was intramuscularly injected once a week for 4 weeks with 1 μg inclusion body containing rGH per gram fish body weight. The result showed that rGH in molecular weight of about 25 kDa was obtained. Fish injected with rGH of El-mGH, Cc-mGH and Og-mGH grew 20.94%, 18.09%, and 16.99% faster, respectively, compared with the control. This result indicated that the three rGH produced in E. coli possessed biological activity when tested on Nile tilapia and further research is needed to find its effect on the growth of other aquaculture fish species.